Positive plate, battery monomer, battery and electric device
By using the layering setting of the ternary system materials and polyanionic positive electrode material layers of single crystal particles and polycrystalline particles in the positive electrode sheet, the problem of insufficient compaction density and energy density of the positive electrode sheet is solved, and the performance and stability of the battery are improved sex.
Patent Information
- Application Number
- CN202310802214.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
In the cathode sheet of lithium-ion batteries, the layering arrangement of multi-layer cathode active materials cannot effectively improve the compaction density and energy density, resulting in uneven current phenomena and a decrease in capacity retention rate.
The ternary system materials using single-crystal and polycrystalline particles are used in the positive electrode active material layer, and by controlling the relationship between particle grading and layer thickness, the compaction density and energy density of the positive electrode sheet are improved, while the ion transport performance is relatively good. A weak polyanionic positive electrode material layer is provided on the surface of the first positive electrode active material layer to reduce current unevenness.
The compaction density and energy density of the positive electrode sheet are improved, the polarization and internal resistance of the battery are weakened, the capacity retention and rate performance are improved, and the cycle stability and safety performance of the battery are enhanced.
Smart Images

Figure CN119230772A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a battery cell, a battery and an electrical device. Background Art
[0002] In a positive electrode sheet using multiple positive electrode active materials, in order to reduce the possibility of current unevenness between the positive electrode active materials, the positive electrode active materials are usually arranged in layers. Usually, the particle sizes of different positive electrode active materials are different. The layered arrangement method cannot give full play to the grading advantage of the particles, and the compaction density of the entire positive electrode sheet needs to be improved. Summary of the invention
[0003] In view of the above problems, the present application provides a positive electrode sheet, a battery cell, a battery and an electrical device, which can improve the compaction density of the positive electrode sheet.
[0004] In a first aspect, the present application provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode active material layer, the positive electrode active material layer comprising a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer comprising a first positive electrode active material, the first positive electrode active material comprising a ternary system material, the ternary system material comprising single crystal particles and polycrystalline particles, the second positive electrode active material layer comprising a second positive electrode active material, the second positive electrode active material comprising a polyanion positive electrode material, the mass proportion of the single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfies the following relationship:
[0005]
[0006] In the technical solution of the embodiment of the present application, a ternary system material of single crystal particles and polycrystalline particles is used in the first positive electrode active material layer, and the mass proportion of the single crystal particles is controlled by w 单 , the particle size D of the single crystal particles 单 , the mass proportion of polycrystalline particles w 多 , the particle size D of polycrystalline particles 多 satisfy This allows a good particle gradation to be formed between the smaller single crystal particles and the larger polycrystalline particles, thereby improving the compaction density of the entire positive electrode sheet and increasing its energy density. It also allows the transmission path of Li ions to be within a smaller range, which reduces the increase in polarization and internal resistance of the battery when it is used as a battery, which is beneficial to the performance of the battery. At the same time, the first positive electrode active material and the second positive electrode active material are arranged in layers, which can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby allowing the positive electrode sheet to have a higher capacity retention rate in the early stage of the cycle.
[0007] In some embodiments, the mass proportion of the single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfies the following relationship:
[0008] In the above implementation process, by controlling the mass proportion w of the single crystal particles 单 , the particle size D of the single crystal particles 单 , the mass proportion of polycrystalline particles w 多 , the particle size D of polycrystalline particles 多 satisfy It can further improve the compaction density of the entire positive electrode sheet and increase its energy density.
[0009] In some embodiments, the positive electrode sheet further includes a current collector, the first positive electrode active material layer is disposed on at least one surface of the current collector, and the second positive electrode active material layer is disposed on a surface of the first positive electrode active material layer away from the current collector.
[0010] In the above implementation process, by placing the second positive electrode active material layer with weaker ion transmission performance on the surface of the first positive electrode active material layer, when used as a battery, the second positive electrode active material layer is closer to the negative electrode sheet, making its ion transmission path shorter, which is conducive to improving its ion transmission rate and thus improving its rate performance. At the same time, it can reduce the possibility of side reactions of the ternary system materials, which is more conducive to the electrochemical performance of the positive electrode sheet.
[0011] In some embodiments, the relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: and / or
[0012] The thickness H1 of the first positive electrode active material layer is 5 to 35 μm; and / or
[0013] The thickness H2 of the second positive electrode active material layer is 35 to 80 μm.
[0014] In the above implementation process, the relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer is controlled to satisfy: The thickness H1 of the first positive electrode active material layer is 5 to 35 μm and the thickness H2 of the second positive electrode active material layer is 35 to 80 μm, which can make the amount of the ternary system material in a more appropriate range, so that its performance such as energy density and service life can be fully exerted, and at the same time, it can reduce the probability of its side reactions causing the deterioration of battery performance and safety performance. At the same time, the average transmission distance of the entire second positive electrode active material layer is within a smaller range, which is beneficial to its own ion transmission rate, and at the same time can reduce the weakening of the ion transmission capacity of the first positive electrode active material layer, thereby achieving better rate performance. In addition, the amount of the second positive electrode active material can be within a more appropriate range, so that its performance such as safety performance can be fully exerted.
[0015] In some embodiments, the relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: and / or
[0016] The thickness H1 of the first positive electrode active material layer is 10 to 30 μm; and / or
[0017] The thickness H2 of the second positive electrode active material layer is 40 to 70 μm.
[0018] In some embodiments, the relationship between the mass percentage wNi of the Ni element in the ternary system material, the mass percentage wMn of the Mn element in the ternary system material, the thickness H1 of the first positive electrode active material layer, and the thickness H2 of the second positive electrode active material layer satisfies: and / or
[0019] The mass percentage wNi of the Ni element in the ternary system material to all elements is 20% to 55%; and / or
[0020] The mass percentage wMn of the Mn element in the ternary system material to all elements is 5% to 25%.
[0021] In the above implementation process, the content of Ni in the ternary system material is positively correlated with the probability of its side reaction to a certain extent. The higher the Ni content, the easier it is for the side reaction to occur. The content of Mn in the ternary system material is positively correlated with its structural stability to a certain extent. The higher the Mn content, the higher the structural stability. The thickness of the first positive electrode active material layer is positively correlated with the probability of its side reaction to a certain extent. The thicker the thickness, the more the corresponding content of the first positive electrode active material, and the easier it is for the side reaction to occur. The thickness of the second positive electrode active material layer is positively correlated with the probability of the side reaction of the ternary system material to a certain extent. The thicker the second positive electrode active material layer, the easier it is for the ternary system material to have side reactions. By controlling the mass proportion of Ni wNi, the mass proportion of Mn wMn, the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer, the relationship is satisfied: The mass percentage of Ni element in the ternary system material, wNi, of all elements is 20% to 55%, and the mass percentage of Mn element in the ternary system material, wMn, of all elements is 5% to 25%. This can reduce the probability of side reactions in the ternary system material, while making the positive electrode sheet have better safety and cycle stability, and can also take into account the energy density of the positive electrode sheet.
[0022] In some embodiments, the relationship between the mass percentage wNi of the Ni element in the ternary system material, the mass percentage wMn of the Mn element in the ternary system material, the thickness H1 of the first positive electrode active material layer, and the thickness H2 of the second positive electrode active material layer satisfies: and / or
[0023] The mass percentage wNi of the Ni element in the ternary system material to all elements is 30% to 45%; and / or
[0024] The mass percentage wMn of the Mn element in the ternary system material to all elements is 10% to 20%.
[0025] In some embodiments, the mass proportion of the single crystal particles in the ternary system material is 10% to 40%, and the mass proportion of the polycrystalline particles in the ternary system material is 60% to 90%; and / or
[0026] The volume median particle size of the single crystal particles is 2.5 to 4.5 μm; and / or
[0027] The volume median particle size of the polycrystalline particles is 8 to 10 μm.
[0028] In some embodiments, the polyanion cathode material comprises LiMPO 4, M includes Mn and non-Mn elements, the non-Mn elements include one or both of a first doping element and a second doping element, the first doping element is manganese-doped, and the second doping element is phosphorus-doped.
[0029] Optionally, the first doping element includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge.
[0030] Optionally, the second doping element includes one or more elements of B, S, Si and N.
[0031] Optionally, the polyanion cathode material includes Li 1+x Mn 1-y A y P 1-z R z O 4 , wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.
[0032] Optionally, the polyanion cathode material includes Li h A i Mn 1-j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.
[0033] In some embodiments, the polyanionic cathode material further has a coating layer comprising carbon.
[0034] In the above implementation process, the introduction of a carbon-containing coating layer is utilized to improve the conductivity of the cathode active material. At this time, the structure of the cathode active material is actually a core-shell structure with LiMPO 4 as the core and the surface of the core coated with a coating layer.
[0035] In some embodiments, the ternary system material includes nickel-cobalt-manganese ternary material and its modified materials, and nickel-cobalt-aluminum ternary material and its modified materials.
[0036] In the above implementation process, the modified materials of the nickel-cobalt-manganese ternary material and the nickel-cobalt-aluminum ternary material respectively refer to the materials obtained by doping or coating the nickel-cobalt-manganese ternary material or the nickel-cobalt-aluminum ternary material.
[0037] In some embodiments, the ternary system material includes Li a Ni b Co c M1 d M2 e O f R g , where 0.75 ≤ a ≤ 1.2, 0.3 < b < 1.0, 0 < c < 0.4, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is selected from one or two elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.
[0038] In a second aspect, the present application provides a positive electrode sheet, the positive electrode sheet includes a cathode active material layer and a current collector, the cathode active material layer includes a first cathode active material layer and a second cathode active material layer, the first cathode active material layer is disposed on at least one surface of the current collector, and the second cathode active material layer is disposed on the surface of the first cathode active material layer away from the current collector; the first cathode active material layer includes a first cathode active material, the first cathode active material includes a ternary system material, the ternary system material includes single crystal particles and polycrystalline particles, the second cathode active material layer includes a second cathode active material, the second cathode active material includes a polyanion cathode material, the mass ratio w 单 of the single crystal particles in the ternary system material, the volume median diameter D 单 in μm of the single crystal particles, the mass ratio w 多 of the polycrystalline particles in the ternary system material, and the volume median diameter D 多 in μm of the polycrystalline particles satisfy the following relationship:
[0039] In the technical solution of the embodiment of the present application, a ternary system material of single crystal particles and polycrystalline particles is used in the first positive electrode active material layer, and the mass proportion of the single crystal particles is controlled by w 单 , the particle size D of the single crystal particles 单 , the mass proportion of polycrystalline particles w 多 , the particle size D of polycrystalline particles 多 satisfy It makes it possible to form a good particle gradation between the smaller single crystal particles and the larger polycrystalline particles, thereby improving the compaction density of the entire positive electrode sheet and increasing its energy density. It can also make the transmission path of Li ions in a smaller range, and when it is used as a battery, it can reduce the increase in polarization and internal resistance of the battery, which is beneficial to the performance of the battery. At the same time, the first positive electrode active material and the second positive electrode active material are arranged in layers, which can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby making the positive electrode sheet have a higher capacity retention rate in the early stage of the cycle. In addition, polyanion positive electrode materials usually show good safety performance, and ternary system materials usually show higher energy density. Using polyanion positive electrode materials as the second positive electrode active material and ternary system materials as the first positive electrode active material can make the positive electrode sheet have both higher safety performance and higher energy density. In addition, a second positive electrode active material layer with weaker ion transport performance is arranged on the surface of the first positive electrode active material layer. When used as a battery, the second positive electrode active material layer is closer to the negative electrode sheet, making its ion transport path shorter, which is beneficial to improving its ion transport rate and thus improving its rate performance.
[0040] In a third aspect, the present application provides a battery cell, the battery cell comprising the positive electrode sheet provided in the first aspect or the second aspect.
[0041] In a fourth aspect, the present application provides a battery, the battery comprising the battery cell provided in the third aspect.
[0042] In a fifth aspect, the present application provides an electrical device, which includes the battery cell provided in the third aspect or the battery provided in the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0044] Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application;
[0045] Figure 2A schematic diagram of the exploded structure of a secondary battery provided in some embodiments of the present application;
[0046] Figure 3 A schematic diagram of the structure of a battery cell provided in some embodiments of the present application;
[0047] Figure 4 An exploded view of a battery cell provided for some embodiments of the present application;
[0048] Figure 5 A first structural schematic diagram of a positive electrode sheet provided in some embodiments of the present application;
[0049] Figure 6 A second structural schematic diagram of a positive electrode sheet provided in some embodiments of the present application;
[0050] Figure 7 A flow chart of a method for preparing a positive electrode sheet provided in some embodiments of the present application.
[0051] The reference numerals in the specific implementation manner are as follows:
[0052] 1000-vehicle; 100-secondary battery; 200-motor; 300-controller; 10-housing; 11-accommodating space; 12-first part; 13-second part; 20-battery cell; 21-housing; 211-opening; 22-end cover assembly; 221-end cover; 222-electrode terminal; 23-electrode assembly; 231-positive electrode sheet; 2311-positive current collector; 2312-positive active material layer; 2312a-first positive active material layer; 2312b-second positive active material layer; 24-current collecting member; 25-insulating protection member. DETAILED DESCRIPTION
[0053] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0055] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0056] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0057] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0058] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0059] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0060] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0061] At present, from the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.
[0062] The power battery can be a lithium-ion battery, which is widely used in portable electronic devices, electric vehicles and other fields. In the production process of lithium-ion secondary battery electrode plates, a single-layer coating is usually used to coat the required active material on the current collector. With the increase in energy density and safety performance requirements, some people have proposed the use of positive electrode active materials with high energy density characteristics such as ternary system materials and positive electrode active materials with high safety performance characteristics such as polyanion positive electrode materials to take into account energy density and safety performance.
[0063] However, when a positive electrode active material with high energy density characteristics and a positive electrode active material with high safety performance characteristics are directly incorporated into a positive electrode active material layer, current unevenness is likely to occur between the two positive electrode active materials in the positive electrode active material layer. This phenomenon will cause the positive electrode sheet to decay rapidly in the early stage of the cycle, which will have a great impact on the capacity retention rate of the positive electrode sheet.
[0064] In order to further improve the problem of rapid attenuation of the electrode in the early stage of the cycle, the two active materials can be arranged in layers. However, the particle size of the ternary system material is often an order of magnitude larger than that of the polyanion positive electrode material. After the layered arrangement, the particle grading advantages of the two cannot be brought into play, resulting in the compaction density of the entire positive electrode sheet needs to be improved.
[0065] Based on the above considerations, in order to increase the compaction density of the positive electrode sheet and improve its energy density. The present application proposes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer includes a first positive electrode active material, the first positive electrode active material includes a ternary system material, the ternary system material includes single crystal particles and polycrystalline particles, the second positive electrode active material layer includes a second positive electrode active material, the second positive electrode active material includes a polyanion positive electrode material, the mass proportion of the single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfies the following relationship:
[0066] In such a positive electrode sheet, a ternary system material of single crystal particles and polycrystalline particles is used in the first positive electrode active material layer, and the mass proportion of the single crystal particles is controlled. 单 , the particle size D of the single crystal particles 单 , the mass proportion of polycrystalline particles w 多 , the particle size D of polycrystalline particles 多 satisfy This allows a good particle gradation to be formed between the smaller single crystal particles and the larger polycrystalline particles, thereby improving the compaction density of the entire positive electrode sheet and increasing its energy density. It also allows the transmission path of Li ions to be within a smaller range, which reduces the increase in polarization and internal resistance of the battery when it is used as a battery, which is beneficial to the performance of the battery. At the same time, the first positive electrode active material and the second positive electrode active material are arranged in layers, which can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby allowing the positive electrode sheet to have a higher capacity retention rate in the early stage of the cycle.
[0067] The positive electrode sheet can be used to prepare an electrode assembly, which can be used, but not limited to, in electrical devices such as vehicles, ships or aircraft. A power supply system of the electrical device can be composed of a battery cell, a secondary battery, etc. disclosed in the present application, so that it is conducive to giving full play to the effect of the positive electrode material with a high ultimate compaction density on the compaction density of the entire positive electrode active material layer, achieving a good improvement in the compaction density of the entire positive electrode active material layer, thereby improving the energy density of the positive electrode sheet and achieving an increase in the capacity of the battery cell.
[0068] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0069] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.
[0070] Please refer to Figure 1 , Figure 1A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A secondary battery 100 is provided inside the vehicle 1000, and the secondary battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The secondary battery 100 may be used to power the vehicle 1000, for example, the secondary battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 300 and a motor 200, and the controller 300 is used to control the secondary battery 100 to power the motor 200, for example, for starting, navigating and driving the vehicle 1000.
[0071] In some embodiments of the present application, the secondary battery 100 can be used not only as an operating power source for the vehicle 1000 , but also as a driving power source for the vehicle 1000 , replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000 .
[0072] In the present application, the secondary battery 100 refers to a single physical module including multiple battery cells 20 to provide higher voltage and capacity, which can be in the form of a battery pack, a battery module, etc. The secondary battery 100 can include a box 10 for encapsulating multiple battery cells 20, and the box 10 can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.
[0073] Figure 2 This is a schematic diagram of the exploded structure of a secondary battery 100 provided in some embodiments of the present application. Figure 2 The secondary battery 100 includes a housing 10 and a battery cell 20 , and the battery cell 20 is accommodated in the housing 10 .
[0074] The box body 10 is used to provide a storage space 11 for the battery cell 20. In some embodiments, the box body 10 may include a first portion 12 and a second portion 13, and the first portion 12 and the second portion 13 cover each other to define the storage space 11 for accommodating the battery cell 20. Of course, the connection between the first portion 12 and the second portion 13 can be sealed by a sealing member (not shown in the figure), and the sealing member can be a sealing ring, a sealant, etc.
[0075] The first part 12 and the second part 13 can be in various shapes, such as a cuboid, a cylinder, etc. The first part 12 can be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20, and the second part 13 can also be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20. The opening side of the second part 13 covers the opening side of the first part 12, thereby forming a box body 10 with a receiving space 11. Of course, if Figure 2As shown, the first part 12 may be a hollow structure with one side open, and the second part 13 may be a plate-like structure. The second part 13 covers the open side of the first part 12 to form a box body 10 with an accommodating space 11.
[0076] In the secondary battery 100, there are multiple battery cells 20, and the multiple battery cells 20 can be connected in series, in parallel, or in a mixed connection. The mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 can be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10; of course, multiple battery cells 20 can also be connected in series, in parallel, or in a mixed connection to form a battery module, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery cell 20 can be cylindrical, flat, rectangular, or in other shapes. Figure 2 The example shows that the battery cell 20 is in a square shape.
[0077] In some embodiments, the secondary battery 100 may further include a busbar component (not shown), and the multiple battery cells 20 may be electrically connected via the busbar component to achieve series connection, parallel connection, or mixed connection of the multiple battery cells 20 .
[0078] Figure 3 This is a schematic diagram of the structure of a battery cell 20 provided in some embodiments of the present application. Figure 4 This is an exploded view of a battery cell 20 provided in some embodiments of the present application. Figure 3 and Figure 4 The battery cell 20 may include a housing 21 , an end cap assembly 22 and an electrode assembly 23 . The housing 21 has an opening 211 , the electrode assembly 23 is accommodated in the housing 21 , and the end cap assembly 22 is used to cover the opening 211 .
[0079] The shape of the housing 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is a rectangular parallelepiped structure, the housing 21 can be a rectangular parallelepiped structure. Figure 3 and Figure 4 The case where the housing 21 and the electrode assembly 23 are square is exemplarily shown.
[0080] The shell 21 may also be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0081] The end cap assembly 22 includes an end cap 221 and an electrode terminal 222. The end cap assembly 22 is used to seal the opening 211 of the housing 21 to form a closed installation space (not shown), and the installation space is used to accommodate the electrode assembly 23. The installation space is also used to accommodate an electrolyte, such as an electrolyte. The end cap assembly 22 is a component for outputting the electrical energy of the electrode assembly 23. The electrode terminal 222 in the end cap assembly 22 is used to be electrically connected to the electrode assembly 23, that is, the electrode terminal 222 is electrically connected to the tab of the electrode assembly 23. For example, the electrode terminal 222 is connected to the tab through the current collecting member 24 to achieve electrical connection between the electrode terminal 222 and the tab.
[0082] It should be noted that the opening 211 of the shell 21 can be one or two. If the opening 211 of the shell 21 is one, the end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22, and the two electrode terminals 222 are respectively used to electrically connect to the positive pole ear and the negative pole ear of the electrode assembly 23. If the opening 211 of the shell 21 is two, for example, the two openings 211 are provided on opposite sides of the shell 21, and the end cap assembly 22 can also be two, and the two end cap assemblies 22 are respectively covered at the two openings 211 of the shell 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal, which is used to electrically connect to the positive pole ear of the electrode assembly 23; the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal, which is used to electrically connect to the negative electrode sheet of the electrode assembly 23.
[0083] In some embodiments, Figure 4 As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the periphery of the electrode assembly 23, and the insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the housing 21. Exemplarily, the insulating protective member 25 is a tape bonded to the periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 is arranged around the periphery of the multiple electrode assemblies 23, and the multiple electrode assemblies 23 are formed into an integral structure to keep the electrode assembly 23 structurally stable.
[0084] The electrode assembly 23 includes a positive electrode sheet 231, a negative electrode sheet and a separator. The positive electrode sheet 231 includes a positive electrode collector 2311 and a positive electrode active material layer 2312. The positive electrode active material layer 2312 is coated on the surface of the positive electrode collector 2311. The positive electrode collector 2311 not coated with the positive electrode active material layer 2312 protrudes from the positive electrode collector 2311 coated with the positive electrode active material layer 2312. The positive electrode collector 2311 not coated with the positive electrode active material layer 2312 serves as a positive electrode tab.
[0085] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on the surface of the negative electrode current collector, the negative electrode current collector not coated with the negative electrode active material layer protrudes from the negative electrode current collector coated with the negative electrode active material layer, and the negative electrode current collector not coated with the negative electrode active material layer serves as a negative electrode tab. The material of the negative electrode current collector may be copper, and the negative electrode active material may be carbon or silicon, etc. In order to ensure that a large current passes without melting, the number of positive electrode tabs is multiple and stacked together, and the number of negative electrode tabs is multiple and stacked together. The material of the isolation film may be PP (polypropylene) or PE (polyethylene), etc. In addition, the electrode assembly 23 may be a wound electrode assembly or a laminated electrode assembly, and the embodiments of the present application are not limited thereto.
[0086] Figure 5 This is a first structural schematic diagram of the positive electrode sheet 231 provided in some embodiments of the present application. Figure 6 A second structural schematic diagram of the positive electrode sheet 231 provided in some embodiments of the present application; see Figure 5 and Figure 6 , an embodiment of the present application provides a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer includes a first positive electrode active material, the first positive electrode active material includes a ternary system material, the ternary system material includes single crystal particles and polycrystalline particles, the second positive electrode active material layer includes a second positive electrode active material, the second positive electrode active material includes a polyanion positive electrode material, the mass proportion of the single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfies the following relationship:
[0087] The positive electrode active material layer 2312 is attached to at least part of the surface of the positive electrode collector 2311. The first positive electrode active material layer 2312a and the second active material layer in the positive electrode active material layer 2312 can both be in direct contact with the positive electrode collector 2311. In other words, the positional relationship between the first positive electrode active material layer 2312a, the second active material layer and the positive electrode collector 2311 can be: the first positive electrode active material layer 2312a is attached to the positive electrode collector 2311, and the second positive electrode active material layer 2312b is attached to the surface of the first positive electrode active material layer 2312a facing away from the positive electrode collector 2311; it can also be: the second positive electrode active material layer 2312b is attached to the positive electrode collector 2311, and the first positive electrode active material layer 2312a is attached to the surface of the second positive electrode active material layer 2312b facing away from the positive electrode collector 2311.
[0088] The material of the positive electrode current collector 2311 may be one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Figure 5 In one embodiment, a first positive electrode active material layer 2312a and a second positive electrode active material layer 2312b are sequentially disposed on one surface of the positive electrode current collector 2311; please continue to refer to Figure 6 In another embodiment, the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b are sequentially disposed on both surfaces of the positive electrode current collector 2311. It should be noted that this is only an example of how this solution can be implemented. In other embodiments, the positions of the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b may be swapped.
[0089] For lithium-ion batteries, the first positive electrode active material and the second positive electrode active material in the first positive electrode active material and the second positive electrode active material refer to substances capable of inserting and extracting lithium ions.
[0090] Ternary system materials usually include two types: NCA and NCM. Among them, NCA is widely used due to its long life, large capacity, and high energy density; while NCM combines the advantages of three types of positive electrode materials: lithium cobalt oxide, lithium nickel oxide, and lithium manganese oxide, and has an obvious ternary synergistic effect.
[0091] A single crystal refers to a crystal in which the particles are regularly and periodically arranged in three-dimensional space, or the whole crystal is composed of the same spatial lattice in three-dimensional direction, and the arrangement of particles in the space of the whole crystal is long-range orderly. A polycrystal is a collection of single crystals with many oriented grains. A particle refers to a geometric body with a specific shape within a certain size range.
[0092] The median particle size (Dv50) is the particle size corresponding to 50% of the cumulative amount in the volume particle size cumulative distribution diagram. The volume particle size cumulative distribution diagram, also known as the differential distribution diagram of the particle size, is a curve drawn with the particle size as the horizontal coordinate and the differential distribution of the content at different particle sizes as the vertical coordinate, which can more accurately reflect the particle size distribution characteristics of the material particles. Among them, a laser particle size analyzer can be used to measure the volume particle size distribution of the material, and an interval particle size distribution curve can be drawn. When the median particle size of the positive electrode active material in the active material layer of the electrode sheet is measured, the positive electrode active material layer can be removed and immersed in the solvent NMP to wash out the binder in the positive electrode active material layer to obtain the powder material of the positive electrode active material layer, and the powder material is dried and then detected using a laser particle size analyzer with a model of Mastersizer3000 to obtain a volume particle size cumulative distribution diagram. The median particle size of polycrystalline particles and single crystal particles can be obtained according to the peak in the volume particle size cumulative distribution diagram.
[0093] The median particle size (Dv50) of polycrystalline particles refers to: when the polycrystalline particles are added up from small to large, and the total volume accounts for 50%, the particle size of the polycrystalline particles is the median particle size Dv50. The median particle size (Dv50) of single crystal particles refers to: when the single crystal particles are added up from small to large, and the total volume accounts for 50%, the particle size of the single crystal particles is the median particle size Dv50.
[0094] Polyanion positive electrode materials are a general term for a series of compounds containing tetrahedral or octahedral anion structural units (XOm)n-. They have the advantages of high charge and discharge voltage, large energy storage capacity, fast charge and discharge capability and good cycle stability. Their synthesis methods mainly include: high temperature solid phase method, sol-gel method, hydrothermal method, electrospinning method, etc.
[0095] The mass ratio of single crystal particles and polycrystalline particles can be obtained by quantitatively distinguishing the distribution ratio of single crystal particles and polycrystalline particles using SEM test images.
[0096] By using a ternary system material of single crystal particles and polycrystalline particles in the first positive electrode active material layer, and controlling the mass proportion w of the single crystal particles 单 , the particle size D of the single crystal particles 单 , the mass proportion of polycrystalline particles w 多 , the particle size D of polycrystalline particles 多 satisfy This allows a good particle gradation to be formed between the smaller single crystal particles and the larger polycrystalline particles, thereby improving the compaction density of the entire positive electrode sheet and increasing its energy density. It also allows the transmission path of Li ions to be within a smaller range, which reduces the increase in polarization and internal resistance of the battery when it is used as a battery, which is beneficial to the performance of the battery. At the same time, the first positive electrode active material and the second positive electrode active material are arranged in layers, which can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby allowing the positive electrode sheet to have a higher capacity retention rate in the early stage of the cycle.
[0097] For example, the mass proportion of single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfied relationship: The value of can be 0.02, 0.04, 0.06, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.26, 0.28, 0.30, 0.32, 0.34, 0.36, 0.38, 0.40, 0.42, 0.44 or 0.45, etc., and it can also be any value in the range of 0.02 to 0.45.
[0098] In the technical solutions of some embodiments of the present application, the mass proportion of the single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfies the following relationship: By controlling the mass proportion w of the single crystal particles 单 , the particle size D of the single crystal particles 单 , the mass proportion of polycrystalline particles w 多 , the particle size D of polycrystalline particles 多 satisfy It can further improve the compaction density of the entire positive electrode sheet and increase its energy density.
[0099] In the technical solutions of some embodiments of the present application, the positive electrode sheet 231 also includes a current collector, the first positive electrode active material layer is arranged on at least one surface of the current collector, and the second positive electrode active material layer 2312b is arranged on the surface of the first positive electrode active material layer 2312a away from the current collector. By arranging the second positive electrode active material layer 2312b with weaker ion transmission performance on the surface of the first positive electrode active material layer 2312a, when used as a battery, the second positive electrode active material layer 2312b is closer to the negative electrode sheet 232, so that its ion transmission path is shorter, which is conducive to improving its ion transmission rate and thus improving its rate performance. At the same time, it can reduce the possibility of side reactions of the ternary system materials, which is more conducive to the electrochemical performance of the positive electrode sheet.
[0100] In the technical solutions of some embodiments of the present application, the relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: The thickness H1 of the first positive electrode active material layer is 5 to 35 μm; the thickness H2 of the second positive electrode active material layer is 35 to 80 μm. The relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer is controlled to satisfy: The thickness H1 of the first positive electrode active material layer is 5 to 35 μm and the thickness H2 of the second positive electrode active material layer is 35 to 80 μm, which can make the amount of the ternary system material in a more appropriate range, so that its performance such as energy density and service life can be fully exerted, and at the same time, it can reduce the probability of its side reactions causing the deterioration of battery performance and safety performance. At the same time, the average transmission distance of the entire second positive electrode active material layer is within a smaller range, which is beneficial to its own ion transmission rate, and at the same time can reduce the weakening of the ion transmission capacity of the first positive electrode active material layer, thereby achieving better rate performance. In addition, the amount of the second positive electrode active material can be within a more appropriate range, so that its performance such as safety performance can be fully exerted.
[0101] Exemplarily, the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfy the relationship The value of can be 0.8, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16, etc., and it can also be any value in the range of 0.8 to 16. The thickness H1 of the first positive electrode active material layer can be 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 21 μm, 23 μm, 25 μm, 27 μm, 29 μm, 31 μm, 33 μm or 35 μm, etc., and it can also be any value in the range of 5 to 35 μm. The thickness H2 of the second positive electrode active material layer can be 35μm, 37μm, 39μm, 40μm, 43μm, 45μm, 47μm, 49μm, 51μm, 53μm, 55μm, 57μm, 59μm, 61μm, 63μm, 65μm, 67μm, 69μm, 71μm, 73μm, 75μm, 77μm, 79μm and 80μm, etc., and it can also be any value in the range of 35 to 80μm.
[0102] In the technical solutions of some embodiments of the present application, the relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: The thickness H1 of the first positive electrode active material layer is 10 to 30 μm; the thickness H2 of the second positive electrode active material layer is 40 to 70 μm.
[0103] In the technical solutions of some embodiments of the present application, the relationship between the mass percentage wNi of the Ni element in the ternary system material, the mass percentage wMn of the Mn element in the ternary system material, the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: The mass percentage wNi of the Ni element in the ternary system material is 20% to 55%; the mass percentage wMn of the Mn element in the ternary system material is 5% to 25%. It should be noted that the values of H1 and H2 are both in μm.
[0104] The content test of Ni and Mn in NCM material can be as follows: take 0.4g of the NCM material layer powder of the electrode piece into a 25ml beaker, add 2ml to 5ml nitric acid, leave it overnight, then place it on an electric hot plate, heat it at about 100°C (use a voltage-regulating transformer to adjust the input voltage and control the temperature), add 0.5ml of perchloric acid after the powder is digested, and heat it at about 140°C until the white smoke is gone. The residue should be white, otherwise nitric acid and perchloric acid should be added again to repeat the digestion, and finally use 7% (volume % of acid, the same below) hydrochloric acid to dissolve and extract. After the volume is fixed to an appropriate volume depending on the content of the element to be tested, the mass fraction of Ni, Co, Mn, and Li is tested on the ICP-OES test instrument. The mass of different elements can be calculated based on the mass of the powder and the mass fraction of different elements, and the Ni and Mn contents can be confirmed by different mass ratios.
[0105] The content of Ni in the ternary system material is positively correlated with the probability of its side reaction to a certain extent. The higher the Ni content, the easier it is for the side reaction to occur. The content of Mn in the ternary system material is positively correlated with its structural stability to a certain extent. The higher the Mn content, the higher the structural stability. The thickness of the first positive electrode active material layer is positively correlated with the probability of its side reaction to a certain extent. The thicker the thickness, the higher the content of the corresponding first positive electrode active material, and the easier it is for the side reaction to occur. The thickness of the second positive electrode active material layer is positively correlated with the probability of the side reaction of the ternary system material to a certain extent. The thicker the second positive electrode active material layer, the easier it is for the ternary system material to have side reactions. By controlling the mass proportion of Ni wNi, the mass proportion of Mn wMn, the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer, the relationship is satisfied: The mass percentage of Ni element in the ternary system material, wNi, of all elements is 20% to 55%, and the mass percentage of Mn element in the ternary system material, wMn, of all elements is 5% to 25%. This can reduce the probability of side reactions in the ternary system material, while making the positive electrode sheet have better safety and cycle stability, and can also take into account the energy density of the positive electrode sheet.
[0106] Exemplarily, the mass percentage of Ni element in the ternary system material to all elements wNi, the mass percentage of Mn element in the ternary system material to all elements wMn, the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfy the relationship The value of can be 0.05, 0.5, 1, 1.5, 2, 2.5, 3 or 3.5, etc., and it can also be any value in the range of 0.05 to 3.5. The mass percentage of Ni element in all elements in the ternary system material wNi can be 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54% or 55%, etc., and it can also be any value in the range of 20% to 55%. The mass percentage of Mn element in all elements in the ternary system material wMn can be 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 21%, 23% or 25%, etc., and it can also be any value in the range of 5% to 25%.
[0107] In the technical solutions of some embodiments of the present application, the relationship between the mass percentage wNi of the Ni element in the ternary system material, the mass percentage wMn of the Mn element in the ternary system material, the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: The mass percentage wNi of the Ni element in the ternary system material to all elements is 30% to 45%; the mass percentage wMn of the Mn element in the ternary system material to all elements is 10% to 20%.
[0108] In the technical solutions of some embodiments of the present application, the mass proportion of the single crystal particles in the ternary system material is 10% to 40%, and the mass proportion of the polycrystalline particles in the ternary system material is 60% to 90%; the volume median particle size of the single crystal particles is 2.5 to 4.5 μm; and the volume median particle size of the polycrystalline particles is 8 to 10 μm.
[0109] Exemplarily, the mass proportion of single crystal particles in the ternary system material can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38% or 40%, etc., which can also be any value in the range of 10% to 40%. The mass proportion of polycrystalline particles in the ternary system material can be 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88% or 90%, etc., which can also be any value in the range of 60% to 90%. The volume median particle size of the single crystal particles can be 2.5 μm, 2.7 μm, 2.9 μm, 3.1 μm, 3.3 μm, 3.5 μm, 3.7 μm, 3.9 μm, 4.1 μm, 4.3 μm or 4.5 μm, etc., and it can also be any value in the range of 2.5 to 4.5 μm. The volume median particle size of the polycrystalline particles can be 8 μm, 8.2 μm, 8.4 μm, 8.6 μm, 8.8 μm, 9.0 μm, 9.2 μm, 9.4 μm, 9.6 μm, 9.8 μm or 10 μm, etc., and it can also be any value in the range of 8 to 10 μm.
[0110] In the technical solutions of some embodiments of the present application, the second positive electrode active material includes a polyanion positive electrode material. Optionally, the polyanion positive electrode material includes LiMPO 4 , M includes Mn and non-Mn elements.
[0111] It should be noted that the above-mentioned LiMPO 4 It is not a specific molecular structure formula, but a general expression of lithium manganese phosphate.
[0112] In the technical solutions of some embodiments of the present application, the non-Mn element includes one or both of a first doping element and a second doping element, the first doping element is manganese-doped, and the second doping element is phosphorus-doped.
[0113] In the technical solutions of some embodiments of the present application, the first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge.
[0114] In the technical solutions of some embodiments of the present application, the first doping element includes at least two of Fe, Ti, V, Ni, Co and Mg.
[0115] In the technical solutions of some embodiments of the present application, the second doping element includes one or more elements selected from the group consisting of B, S, Si and N.
[0116] In the technical solutions of some embodiments of the present application, the second positive electrode active material includes Li 1+xMn 1-y A y P 1-z R z O 4 , Li 1+x Mn 1-y A y P 1-z R z O 4 wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.
[0117] In the technical solutions of some embodiments of the present application, the compound Li 1+x Mn 1-y AHr 1-z R 4 The preparation method may include the following steps:
[0118] (1) dissolving a manganese source, a source of an element A to be doped at the manganese position, and an acid in a solvent and stirring to generate a suspension of a manganese salt doped with the element A, filtering the suspension and drying the filter cake to obtain a manganese salt doped with the element A;
[0119] (2) adding a lithium source, a phosphorus source, an element R source, a solvent, and the manganese salt doped with element A obtained in step (1) into a reaction container, grinding and mixing to obtain a slurry;
[0120] (3) transferring the slurry obtained in step (2) to a spray drying device for spray drying and granulation to obtain granules;
[0121] (4) Sintering the particles obtained in step (3) to obtain a positive electrode active material.
[0122] In any embodiment, the manganese source may be a manganese-containing substance known in the art that can be used to prepare lithium manganese phosphate. For example, the manganese source may be selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, manganese carbonate, or a combination thereof.
[0123] The acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, organic acid such as oxalic acid, etc., for example, oxalic acid. The source of element R is selected from at least one of sulfate, borate, nitrate and silicate of element R. The source of element A is selected from at least one of simple substance, oxide, phosphate, oxalate, carbonate and sulfate of A.
[0124] In the technical solutions of some embodiments of the present application, the polyanion positive electrode material includes Li h A i Mn 1-j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.
[0125] It should be noted that Li h A i Mn 1-j B j P 1-k C k O 4-l D l The compound is actually a specific LiMPO 4 Materials. The preparation method can refer to Li 1+x Mn 1-y A y P 1-z R z O 4 , no limitation is made here.
[0126] Below is Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 The preparation process is further described as follows: 1. Preparation of doped manganese oxalate: 1.3 mol of MnSO 4 ﹒ H 2 O, 0.7 mol FeSO 4 ﹒ H 2O was fully mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 10L of deionized water and 2mol of dihydrated oxalic acid (in terms of oxalic acid) were added. The reactor was heated to 80°C and stirred at 600rpm for 6 hours. The reaction was terminated (no bubbles were generated) to obtain an Fe-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and then ground to obtain a median particle size Dv 50 2. Preparation of doped lithium manganese phosphate: 1 mol of the above manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO 4 ) 3 , an aqueous solution of 85% phosphoric acid containing 0.999 mol of phosphoric acid, 0.001 mol of H 4 SiO 4 , 0.0005 mol NH 4 HF 2 and 0.005 mol sucrose were added to 20 L of deionized water. The mixture was transferred to a sand mill and fully ground and stirred for 10 hours to obtain a slurry. The slurry was transferred to a spray drying device for spray drying and granulation. The drying temperature was set to 250°C and dried for 4 hours to obtain particles. In a nitrogen (90% volume) + hydrogen (10% volume) protective atmosphere, the above powder was sintered at 700°C for 10 hours to obtain carbon-coated Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 .
[0127] In the technical solutions of some embodiments of the present application, the second positive electrode active material further has a carbon-containing coating layer.
[0128] The introduction of a carbon-containing coating layer improves the conductivity of the positive electrode active material. At this time, the structure of the positive electrode active material is actually LiMPO 4 The core has a core-shell structure in which the surface of the core is covered with a coating layer.
[0129] In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before adding the materials. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0130] In addition, due to the different preparation processes and conditions of the materials, the molar content of the O element is usually not strictly the coefficient of the O element in the chemical formula, and there will be fluctuations, such as Li 1+x Mn 1-y Ay P 1-z R z O 4 The molar content of the oxygen element is not strictly 4.
[0131] For example, the second positive electrode active material may be LiFePO 4 、LiMn 0.1 Fe 0.9 PO 4 、LiMn 0.2 Fe 0.8 PO 4 、LiMn 0.3 Fe 0.7 PO 4 、LiMn 0.4 Fe 0.6 PO 4 、LiMn 0.5 Fe 0.5 PO 4 、LiMn 0.6 Fe 0.4 PO 4 、LiMn 0.7 Fe 0.3 PO 4 、LiMn 0.8 Fe 0.2 PO 4 、LiMn 0.9 Fe 0.1 PO 4 、LiMnPO 4 、LiMn 0.5 Al 0.5 P 0.5 B 0.5 O 4 、LiMn 0.5 Mg 0.5 P 0.5 S 0.5 O 4 etc., LiMPO 4 The M in the formula includes Mn and non-Mn elements, the non-Mn elements include one or both of the first doping element and the second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping. The first doping element includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; the second doping element includes one or more elements of B, S, Si and N.
[0132] In the technical solutions of some embodiments of the present application, the ternary system material includes nickel-cobalt-manganese ternary material and its modified material, and nickel-cobalt-aluminum ternary material and its modified material. Among them, the ternary system material includes nickel-cobalt-manganese ternary material and its modified material, and nickel-cobalt-aluminum ternary material and its modified material.
[0133] In the technical solutions of some embodiments of the present application, the ternary system material includes Li a Ni b Co c M1 d M2 e O f R g , where 0.75 ≤ a ≤ 1.2, 0.3 < b < 1.0, 0 < c < 0.4, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is selected from one or two elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.
[0134] Exemplarily, the ternary system material can be LiNi 0.4 Co 0.2 Mn 0.4 O 2 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 and LiNi 0.7 Co 0.15 Mn 0.15 O 2 etc. Li a Ni b Co c M1 d M2 e O f R g In Li
[0135] It should be noted that the above enumeration of the first positive electrode active material and the second positive electrode active material is only used as an enumeration to illustrate that this solution can be implemented, and is not intended to limit this solution. In other embodiments, those skilled in the art can select specific materials of the first positive electrode active material and the second positive electrode active material according to actual needs, such as the materials listed above and their modified materials, and the modification includes doping or coating.
[0136] After the above introduction to the material and structure of the positive electrode sheet 231 , the preparation method of the positive electrode sheet 231 will be specifically introduced below.
[0137] The preparation method of the positive electrode sheet 231 includes the following steps: preparing a positive electrode active material layer 2312 on a positive electrode current collector 2311, wherein the preparation order of the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b in the positive electrode active material layer 2312 is not limited, and may be: the first positive electrode active material layer 2312a is arranged on at least a portion of the surface of the positive electrode current collector 2311, and the second positive electrode active material layer 2312b is arranged on at least a portion of the surface of the first positive electrode active material away from the positive electrode current collector 2311; or: the second positive electrode active material layer 231 2b is arranged on at least a portion of the surface of the positive electrode collector 2311, and the first positive electrode active material layer 2312a is arranged on at least a portion of the surface of the second positive electrode active material layer 2312b away from the positive electrode collector 2311; the first positive electrode active material layer includes a first positive electrode active material, the first positive electrode active material includes a ternary system material, the ternary system material includes single crystal particles and polycrystalline particles, the second positive electrode active material layer includes a second positive electrode active material, the second positive electrode active material includes a polyanion positive electrode material, and the mass proportion of the single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfies the following relationship:
[0138] The method adopts a ternary system material of single crystal particles and polycrystalline particles in the first positive electrode active material layer, and controls the mass proportion w of the single crystal particles. 单 , the particle size D of the single crystal particles 单 , the mass proportion of polycrystalline particles w 多 , the particle size D of polycrystalline particles 多 satisfy This allows a good particle gradation to be formed between the smaller single crystal particles and the larger polycrystalline particles, thereby improving the compaction density of the entire positive electrode sheet and increasing its energy density. It also allows the transmission path of Li ions to be within a smaller range, reducing the increase in polarization and internal resistance of the battery, which is beneficial to the performance of the battery. At the same time, the first positive electrode active material and the second positive electrode active material are arranged in layers, which can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby allowing the positive electrode sheet to have a higher capacity retention rate in the early stage of the cycle.
[0139] Figure 7 For a flow chart of a method for preparing the positive electrode sheet 231 provided in some embodiments of the present application, please refer to Figure 7 The present application embodiment provides a method for preparing a positive electrode sheet 231, the method comprising:
[0140] S110, preparing a first positive electrode active slurry: dispersing a first positive electrode active material, a binder and a conductive agent in a solvent to form a first positive electrode active slurry. The first positive electrode active material may be the first positive electrode active material described above, for example, a material having a chemical formula of LiNi x Co y Mn z O 2 , (0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1) ternary system material, optionally, a small amount of other positive electrode active materials may be added.
[0141] For the specific selection of the ternary system material, reference may be made to the selection of the ternary system material in the first positive electrode active material layer 2312 a in the aforementioned positive electrode sheet 231 , which will not be described in detail here.
[0142] The binder may be one or more of styrene-butadiene rubber, water-based acrylic resin, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, polyvinyl alcohol and polyvinyl butyral. The conductive agent may be at least one of conductive carbon black, carbon fiber, carbon nanotube, Ketjen black, graphene or acetylene black. The solvent may be one or more of dimethyl glutarate and N-methyl pyrrolidone. A leveling agent, a dispersant, etc. may also be added to the first positive electrode active slurry.
[0143] S120, preparing a second positive electrode active slurry: dispersing a second positive electrode active material, a binder and a conductive agent in a solvent to form a second positive electrode active slurry. The second positive electrode active material may be the second positive electrode active material described above, for example, a material having a chemical formula of LiMn a Fe 1-a PO 4 , (0≤a≤1) polyanion positive electrode material, and optionally a small amount of other positive electrode active materials may be added.
[0144] For the specific selection of the polyanion positive electrode material, reference may be made to the selection of the polyanion positive electrode material in the second positive electrode active material layer 2312 b in the aforementioned positive electrode sheet 231 , which will not be described in detail here.
[0145] The binder, the conductive agent and the solvent may be the binder, the conductive agent and the solvent in the first positive electrode active slurry, etc. The binder in the first positive electrode active slurry may be the same as or different from the binder in the second positive electrode active material; the conductive agent in the first positive electrode active slurry may be the same as or different from the conductive agent in the second positive electrode active material; the solvent in the first positive electrode active slurry may be the same as or different from the solvent in the second positive electrode active material. At the same time, a leveling agent, a dispersant, etc. may also be added to the second positive electrode active slurry, which is not limited in this application.
[0146] S130, preparing the first positive electrode active material layer 2312a: coating the first positive electrode active slurry on the surface of the positive electrode current collector 2311, and then drying to form the first positive electrode active material layer 2312a. The coating can be applied to one surface or both surfaces of the positive electrode current collector 2311 according to requirements.
[0147] The coating method may be: scraping, roller coating, slit coating, etc., which is not limited in this application. It should be noted that step S120 and step S130 can be interchanged or performed simultaneously, which is not limited in this application.
[0148] S140, preparing the second positive electrode active material layer 2312b: coating the second positive electrode active slurry on the surface of the first positive electrode active material layer 2312a, and then drying to form the second positive electrode active material layer 2312b. During coating, the second positive electrode active material layer 2312b can be formed on the surface of the first positive electrode active material layer 2312a according to the situation of the first positive electrode active material layer 2312a.
[0149] S150 , rolling the second positive electrode active material layer 2312 b to obtain the positive electrode sheet 231 .
[0150] It should be noted that the above is only an example of sequentially arranging the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b on the positive electrode current collector 2311. In other embodiments, the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b can be exchanged.
[0151] After the positive electrode sheet 231 is prepared, the first isolation film 233, the positive electrode sheet 231, the second isolation film 233 and the negative electrode sheet 232 are stacked in sequence, wound to form a wound flat structure, and then hot pressed to obtain a wound electrode assembly; or, after the positive electrode sheet 231 is prepared, the positive electrode sheet 231, the isolation film 233, the negative electrode sheet 232, the isolation film 233, and so on, are stacked in sequence to form a stacked electrode assembly.
[0152] The electrode assembly 23 can be used to prepare a battery cell 20 , and the battery cell 20 can be used to prepare a secondary battery 100 and provide electric energy to an electric device.
[0153] Next, one or more embodiments are described in more detail with reference to the following examples. Of course, these examples do not limit the scope of one or more embodiments.
[0154] Examples and Comparative Examples
[0155]
Preparation of positive electrode
[0156] Preparation of the first positive electrode active material layer: The first positive electrode active material LiNi 0.55 Co 0.12 Mn 0.33 O 2 , conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP), wherein the binder polyvinylidene fluoride (PVDF) accounts for 2.5% by mass, and stirred and mixed to obtain a first coating layer slurry; then the slurry is mixed at 90mg / 1540.25mm 2 The mass of the positive electrode active material is evenly coated on the positive electrode current collector and dried to obtain a first positive electrode active material layer.
[0157] Preparation of the second positive electrode active material layer: The second positive electrode active material LiMn 0.6 Fe 0.4 PO 4 , conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP) at a mass ratio of 96.5:1:2.5, and stirred and mixed to obtain a second coating layer slurry; then the slurry is mixed at 200mg / 1540.25mm 2 The mass is evenly coated on the first positive electrode active material layer, and after drying, it is rolled and die-cut to obtain a lithium-ion battery positive electrode sheet.
[0158]
Preparation of negative electrode sheet
[0159] The active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a mass ratio of 90:5:3:2, and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0160]
Preparation of electrolyte
[0161] In an argon atmosphere glove box (H 2 O<0.1ppm, O 2 <0.1ppm), mix the organic solvents ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) in a volume ratio of 1 / 1 / 1, add 1 mol / L LiPF 6 The lithium salt is dispersed uniformly, and then 5% fluoroethylene carbonate is dissolved in the above organic solvent and stirred uniformly to obtain an electrolyte.
[0162]
Isolation film
[0163] A polyethylene film was used as the separator, and its thickness was 7 μm.
[0164]
Preparation of lithium-ion batteries
[0165] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene (PE) porous polymer film) are wound to form the corresponding battery cell, and the battery cell is hot pressed at 90°C, followed by ultrasonic welding of the positive and negative pole tabs. The positive electrode uses aluminum pole tabs, and the negative electrode uses copper pole tabs. The positive and negative pole tabs are located on the same side of the battery cell. The battery cell after the pole tab welding is placed in an aluminum shell of appropriate size for soft connection and top cover welding. The battery cell is vacuum dried at 175°C for 24 hours, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then goes through the processes of static, formation, aging, exhaust, secondary sealing, capacity testing, etc. to obtain a lithium-ion battery product.
[0166] The main parameters of each embodiment and comparative example are shown in the following table:
[0167]
[0168]
[0169] In the above table, the content test of Ni and Mn in NCM material can be as follows: take 0.4g of the NCM material layer powder of the electrode piece into a 25ml beaker, add 2ml to 5ml nitric acid, leave it overnight, then place it on an electric hot plate, heat it at about 100°C (use a voltage-regulating transformer to adjust the input voltage and temperature control), add 0.5ml of perchloric acid after the powder is digested, and heat it at about 140°C until the white smoke is gone. The residue should be white, otherwise nitric acid and perchloric acid should be added again to repeat the digestion, and finally use 7% (volume % of acid, the same below) hydrochloric acid to dissolve and extract. After the volume is fixed to an appropriate volume depending on the content of the element to be measured, the mass fraction of Ni, Co, Mn, and Li can be tested on the ICP-OES test instrument. The mass of different elements can be calculated based on the mass of the powder and the mass fraction of different elements, and the content of Ni and Mn can be confirmed by different mass ratios.
[0170] Embodiment 24
[0171] This embodiment is the same as Embodiment 2 except that the positions of the first positive electrode active material layer and the second positive electrode active material layer are exchanged.
[0172] The performance test was performed on the batteries provided in each embodiment and comparative example, and the performance test specifically included:
[0173] The method for testing the compaction density of the pole piece is as follows: according to the energy density design requirements, the pole piece coating surface density can be determined. After the pole piece is dried and cold pressed, the total thickness of the pole piece is measured using a spiral micrometer, and the coating thickness can be calculated by deducting the thickness of the current collector. Based on the two parameters of coating surface density and coating thickness, the compaction density of the pole piece can be calculated.
[0174] The method of rate performance test is: in an environment of 25℃, charge and discharge test is carried out, and constant current discharge is carried out at a discharge current of 0.33C (i.e., the current value of the theoretical capacity is completely discharged within 3h) until the voltage is 2.5V. Then, constant current charging is carried out at a charging current of 0.33C to a voltage of 4.4V, and constant voltage charging is continued to be carried out to a current of 0.05C. At this time, the battery is in a fully charged state. After the fully charged battery cell is left to stand for 5 minutes, constant current discharge is carried out at a discharge current of 0.33C to 2.5V. The discharge capacity at this time is the actual capacity of the battery cell at 0.33C, recorded as C0. Then, the battery cell is charged to 4.4V at a constant current of 0.33C, and then constant voltage charging is carried out to a current of 0.05C, and it is left to stand for 5 minutes, and then discharged to 2.5V at a constant current of 1C, and the discharge capacity C1 is recorded as the 1C discharge capacity. 1C rate capacity retention rate = (1C discharge capacity / 0.33C discharge capacity) × 100%.
[0175] 25℃ cycle test: The lithium-ion battery product prepared above was charged to 4.4V at 0.33C at 2.5-4.4V in a constant temperature environment of 25℃, and then charged at a constant voltage at 4.4V to a current ≤0.05C, allowed to stand for 5 minutes, and then discharged to 2.5V at 0.33C. The capacity was recorded as Cn (n=1, 2, 3...). The above operation was repeated. After 500 cycles, the capacity retention rate was calculated according to the ratio of C500 / C3 as an examination indicator of the cycle capacity.
[0176] 25℃ cyclic internal resistance growth test: ① Initial internal resistance test: The square shell battery prepared above is charged to 4.4V at 0.33C at 2.5-4.4V in a constant temperature environment of 25℃, and then charged at a constant voltage at 4.4V to a current ≤0.05C. After standing for 30 minutes, the voltage U1 is recorded, and then it is discharged at 1C for 30s, and the voltage at 30s is recorded as U2. The internal resistance 1 = (U1-U2) / 1C; ② Internal resistance test after 500 cycles: After the battery with the initial internal resistance tested is tested for cycle performance according to the cycle test, the internal resistance 2 is tested again. The internal resistance growth rate = (internal resistance 2-internal resistance 1) / internal resistance 1.
[0177] The test results are shown in the following table:
[0178]
[0179]
[0180] It should be noted that the compaction density of Examples 1 to 7 and Comparative Examples 1 to 2 is the maximum compaction density that the pole piece can achieve, while Examples 8 to 24 are compared and evaluated with Example 2, so their compaction density is a parameter that needs to be controlled, and is not the maximum compaction density of the pole piece.
[0181] As can be seen from the above table, the positive electrode sheet provided by the present application has a high compaction density, which can reach 3g / cm 3 It has a higher rate performance, which can reach more than 95%, a higher capacity retention rate, which can reach more than 89% and a lower cycle internal resistance growth rate, which does not exceed 80%.
[0182] By comparing Example 2, Examples 4 to 7 and Comparative Examples 1 to 2, it can be seen that as the mass proportion of the single crystal particles w 单 , the particle size D of the single crystal particles 单 , the mass proportion of polycrystalline particles w 多 , the particle size D of polycrystalline particles 多 Satisfying relationship As the value of gradually increases, the compaction density, rate performance and capacity retention rate of the electrode piece all show a trend of first increasing and then decreasing, and the cycle internal resistance growth rate of the electrode piece shows a trend of first decreasing and then increasing, and the mass proportion of single crystal particles w 单 , the particle size D of the single crystal particles 单 , the mass proportion of polycrystalline particles w 多 , the particle size D of polycrystalline particles 多 Satisfying relationship When the value is in the range of 0.02 to 0.45, the compaction density of the electrode can reach 3g / cm 3 The above, the rate performance can reach more than 98%, the capacity retention rate can reach more than 90%, and the cycle internal resistance growth rate does not exceed 60%. It can be seen that the relationship value of 0.02-0.45 is a better range. At the same time, when the relationship value is 0.15-0.3, the compaction density of the pole piece can reach 3.1g / cm 3 The rate performance can reach about 99%, the capacity retention rate can reach about 94%, and the cycle internal resistance growth rate is about 40%. It can be seen that the relationship value of 0.15 to 0.3 is a better range.
[0183] By comparing Example 2 with Examples 8 to 11, it can be obtained that as the thickness H1 of the first positive electrode active material layer gradually increases, the rate performance and capacity retention rate of the electrode sheet both show a trend of first increasing and then decreasing, and the cycle internal resistance growth rate of the electrode sheet shows a trend of first decreasing and then increasing. When the thickness H1 of the first positive electrode active material layer is in the range of 5 to 35 μm, the rate performance can reach more than 98.9%, the capacity retention rate can reach more than 93.2%, and the cycle internal resistance growth rate does not exceed 50%. It can be seen that the thickness H1 of the first positive electrode active material layer is in a preferred range of 5 to 35 μm.
[0184] By comparing Example 2 with Examples 12 to 15, it can be obtained that as the thickness H2 of the second positive electrode active material layer gradually increases, the rate performance and capacity retention rate of the electrode sheet both show a trend of first increasing and then decreasing, and the cycle internal resistance growth rate of the electrode sheet shows a trend of first decreasing and then increasing. When the thickness H2 of the second positive electrode active material layer is in the range of 35 to 80 μm, the rate performance can reach more than 98.6%, the capacity retention rate can reach more than 92.9%, and the cycle internal resistance growth rate does not exceed 59%. It can be seen that the thickness H2 of the second positive electrode active material layer is in a preferred range of 35 to 80 μm.
[0185] By comparing Example 2 with Examples 16 to 19, it can be seen that as the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer The value of gradually increases, the rate performance and capacity retention rate of the electrode sheet show a trend of first increasing and then decreasing, the cycle internal resistance growth rate of the electrode sheet shows a trend of first decreasing and then increasing, and the relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer When the value is in the range of 1 to 16, the rate performance can reach more than 98.2%, the capacity retention rate can reach more than 92.6%, and the cycle internal resistance growth rate does not exceed 59%. It can be seen that the relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer The value of is in the range of 1 to 16.
[0186] By comparing Example 2 with Examples 20 to 23, it can be seen that the relationship between the mass proportion of Ni wNi, the mass proportion of Mn wMn, the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer is The value of gradually increases, the rate performance and capacity retention rate of the electrode sheet show a trend of first increasing and then decreasing, the cycle internal resistance growth rate of the electrode sheet shows a trend of first decreasing and then increasing, and the relationship between the mass proportion of Ni wNi, the mass proportion of Mn wMn, the thickness of the first positive electrode active material layer H1 and the thickness of the second positive electrode active material layer H2 When the value is in the range of 0.05 to 3.5, the rate performance can reach more than 98.1%, the capacity retention rate can reach more than 90.4%, and the cycle internal resistance growth rate does not exceed 53%. It can be seen that the relationship between the mass proportion of Ni wNi, the mass proportion of Mn wMn, the thickness of the first positive electrode active material layer H1 and the thickness of the second positive electrode active material layer H2 The value of is in the range of 0.05 to 3.5.
[0187] By comparing Example 2 and Example 24, it can be seen that when the ternary system material is arranged in the inner layer, it is more beneficial to the battery's rate performance, capacity retention rate and cycle internal resistance growth rate.
[0188] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer includes a first positive electrode active material, the first positive electrode active material includes a ternary system material, the ternary system material includes single crystal particles and polycrystalline particles, the second positive electrode active material layer includes a second positive electrode active material, the second positive electrode active material includes a polyanion positive electrode material, and the mass proportion of the single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfies the following relationship:
2. The positive electrode sheet according to claim 1, characterized in that: The mass proportion of the single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfies the following relationship:
3. The positive electrode sheet according to any one of claims 1 to 2, characterized in that: The positive electrode sheet further includes a current collector. The first positive electrode active material layer is disposed on at least one surface of the current collector. The second positive electrode active material layer is disposed on a surface of the first positive electrode active material layer away from the current collector.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: and / or The thickness H1 of the first positive electrode active material layer is 5 to 35 μm; and / or The thickness H2 of the second positive electrode active material layer is 35 to 80 μm.
5. The positive electrode sheet according to claim 4, characterized in that: The relationship between the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: and / or The thickness H1 of the first positive electrode active material layer is 10 to 30 μm; and / or The thickness H2 of the second positive electrode active material layer is 40 to 70 μm.
6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The relationship between the mass percentage wNi of the Ni element in the ternary system material, the mass percentage wMn of the Mn element in the ternary system material, the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: and / or The mass percentage wNi of the Ni element in the ternary system material to all elements is 20% to 55%; and / or The mass percentage wMn of the Mn element in the ternary system material to all elements is 5% to 25%.
7. The positive electrode sheet according to claim 6, characterized in that: The relationship between the mass percentage wNi of the Ni element in the ternary system material, the mass percentage wMn of the Mn element in the ternary system material, the thickness H1 of the first positive electrode active material layer and the thickness H2 of the second positive electrode active material layer satisfies: and / or The mass percentage wNi of the Ni element in the ternary system material to all elements is 30% to 45%; and / or The mass percentage wMn of the Mn element in the ternary system material to all elements is 10% to 20%.
8. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: The mass proportion of the single crystal particles in the ternary system material is 10% to 40%, and the mass proportion of the polycrystalline particles in the ternary system material is 60% to 90%; and / or The volume median particle size of the single crystal particles is 2.5 to 4.5 μm; and / or The volume median particle size of the polycrystalline particles is 8 to 10 μm.
9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The ternary system materials include nickel-cobalt-manganese ternary materials and modified materials thereof and nickel-cobalt-aluminum ternary materials and modified materials thereof; and / or The polyanion positive electrode material includes LiMPO4, M includes Mn and non-Mn elements, the non-Mn elements include one or both of a first doping element and a second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping.
10. The positive electrode sheet according to claim 9, characterized in that: The first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; and / or The second doping element includes one or more elements selected from the group consisting of B, S, Si and N.
11. The positive electrode sheet according to claim 9, characterized in that: The polyanion positive electrode material includes Li 1+x Mn 1- y A y P 1-z R z O4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.
12. The positive electrode sheet according to claim 9, characterized in that: The polyanion positive electrode material includes Li h A i Mn 1- j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.
13. The positive electrode sheet according to any one of claims 1 to 12, characterized in that: The polyanion positive electrode material also has a coating layer containing carbon.
14. The positive electrode sheet according to any one of claims 1 to 13, characterized in that: The ternary system material includes Li a Ni b Co c M1 d M2 e O f R g , where 0.75 ≤ a ≤ 1.2, 0.3 < b < 1.0, 0 < c < 0.4, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is selected from one or two elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.
15. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode active material layer and a current collector, the positive electrode active material layer comprises a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer is arranged on at least one surface of the current collector, and the second positive electrode active material layer is arranged on a surface of the first positive electrode active material layer away from the current collector; the first positive electrode active material layer comprises a first positive electrode active material, the first positive electrode active material comprises a ternary system material, the ternary system material comprises single crystal particles and polycrystalline particles, the second positive electrode active material layer comprises a second positive electrode active material, the second positive electrode active material comprises a polyanion positive electrode material, and the mass proportion of the single crystal particles in the ternary system material is w 单 , the volume median particle size D of the single crystal particles in μm 单 , the mass proportion of the polycrystalline particles in the ternary system material w 多 and the volume median particle size D of the polycrystalline particles in μm 多 Satisfies the following relationship:
16. A battery cell, characterized in that: The battery cell comprises the positive electrode sheet according to any one of claims 1 to 15.
17. A battery, characterized in that: The battery comprises the battery cell according to claim 16.
18. An electrical device, characterized in that: The electrical device comprises the battery cell according to claim 16 or the battery according to claim 17.
Citation Information
Patent Citations
Lithium ion battery and positive plate thereof
CN109428051A
Positive pole piece for secondary battery, secondary battery, battery module, battery pack and device
CN114556614A
Positive pole piece and application thereof
CN115498150A
Positive pole piece, secondary battery and electric equipment
CN116314602A
Positive electrode and li-ion battery including the same
US20170092943A1
